2009
DOI: 10.3923/ijps.2009.862.865
|View full text |Cite
|
Sign up to set email alerts
|

Threonine Requirement of Broiler from 22-42 Days

Abstract: Threonine is considered to be the third limiting amino acid for broilers. The aim of this study was to determine the threonine requirement of female broilers from 22 to 42 days of age. Seventy five, one-day of age female broiler chicks (Ross 308) were divided into five dietary treatment groups of similar mean weight, comprising 15 birds each, individually. They were fed a basal starter diet containing 23% CP, 3200 ME kcal/kg, 0.91% threonine and 1.10% lysine (Lys) during the first 3 weeks. At the end of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
2
20
0
Order By: Relevance
“…The results are in the agreement with earlier researcher reported that, the supplementation of 0.80% threonine in female broilers showed better feed conversion ratio (1). However, supplementation of L-threonine in broilers showed better feed conversion ratio (2,18).…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 83%
See 1 more Smart Citation
“…The results are in the agreement with earlier researcher reported that, the supplementation of 0.80% threonine in female broilers showed better feed conversion ratio (1). However, supplementation of L-threonine in broilers showed better feed conversion ratio (2,18).…”
Section: Feed Conversion Ratio (Fcr)supporting
confidence: 83%
“…Adequate digestible Threonine levels are needed to support optimum growth (13) plays an important role as precursor of lysine and serine (17). Threonine improves the livability of heat stressed broilers (1). Increased dietary threonine concentration is known to improve nitrogen retention in broiler chicks; therefore changing level of threonine concentration is an important tool to improve nitrogen utilization (7).…”
Section: Introductionmentioning
confidence: 99%
“…Threonine participates in protein synthesis and its catabolism produces many products important in metabolism. Threonine is considered as the third limiting amino acid after Met and Lys for broiler chicks (Kidd et al, 1999;Ayasan and Okan, 2006;Baylan et al, 2006;Ayasan et al, 2009). Kidd (2000) reported that L-Thr deficiency resulted in decreasing utilization of TSAA and Lys.…”
Section: Introductionmentioning
confidence: 99%
“…Thr is a typically deficient amino acid in corn, sorghum and soybean meal based rations and it becomes one of the major factors in limiting the birds' performance (Kidd, 2000). Supplementation of Thr in the diets of broiler chicks and white Pekin ducklings was reported to improve their growth performance (Horn et al, 2010;Ayasan & Okan, 2011). Khan et al (2006) conducted an experiment on commercial broiler chicks 20~35d of age with different levels of digestible Thr and observed significant improvement in body weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…It is the third most limiting amino acid and plays an important role in animal growth and development (Ayasan et al, 2009;Canogullari et al, 2009;Xie et al, 2014). Thr is a typically deficient amino acid in corn, sorghum and soybean meal based rations and it becomes one of the major factors in limiting the birds' performance (Kidd, 2000).…”
Section: Introductionmentioning
confidence: 99%